Disruption of a selective vesicle pool upon retrograde amnesia dissociates memory at presynaptic terminals - Shun Hiramatsu; Kaito Kabetani; Shu Kondo; Hiromu Tanimoto (Proceedings of the National Academy of Sciences, 2026)
A single learning episode induces both labile and consolidated forms of aversive olfactory memory in Drosophila melanogaster . Retrograde amnesia triggered by post-learning perturbations specifically impairs the labile memory. However, synaptic mechanisms for this selectivity remain elusive. Here, we show that diverse amnestic treatments, such as concussion, commonly disrupt the presynaptic clustering of Synapsin, which is required for anesthesia-sensitive memory. Consistently, targeted knockout of synaptojanin , a key regulator of the endocytic pathway, selectively impaired labile memory and the Synapsin-associated vesicles. In contrast, we identified Rab3, a small GTPase that regulates the late steps of vesicle exocytosis at the active zone, as selectively required for anesthesia-resistant memory. Rab3 hyperactivation enhanced its association with vesicles while displacing Synapsin. Strikingly, this manipulation biased memory toward stabilization at the cost of the labile component. We thus propose distinct vesicle pools at the presynaptic terminal underlie the formation of labile and consolidated memories. Thus, our work offers a molecular framework for controlling memory stability through targeted manipulation of vesicle dynamics.